Cryptanalysis of a modern rotor machine in a multicast setting. Issue 6 (1st November 2016) - Kepley, Shane; Russo, David; Steinwandt, Rainer
ABSTRACT: At FSE '93, Anderson presented a modern byte-oriented rotor machine that is suitable for fast software implementation. Building on a combination of chosen ciphertexts and chosen plaintexts, the authors show that in a setting with multiple recipients, the recovery of an (equivalent) secret key can be feasible within minutes in a standard computer algebra system.